2020
DOI: 10.1002/open.202000062
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the σ‐Hole in Halogen Atoms: a Valence Bond Perspective

Abstract: A detailed Valence Bond-Spin Coupled analysis of a series of halogenated molecules is here reported, allowing to get a rigorous ab initio demonstration of the qualitative models previously proposed to explain the origin of halogen bonding. The concepts of σ-hole and negative belt observed around the halogen atoms in the electrostatic potential maps are here interpreted by analysis of the relevant Spin Coupled orbitals.The role of specific intermolecular interactions in driving selfassembling of molecular and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Despite the presence of many records in the CCDC highlighted in this revisit, theoretical studies centering on the halogen-bond-forming ability of halogen’s electrophilic π-/p-holes (or π-/p-belts) in molecular entities with nucleophiles are rare and surely an important area worthy of further investigation. The development of a hole/belt may be realized as a result of “bond polarization” within the domain of the molecule, a view consonant with that of others …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Despite the presence of many records in the CCDC highlighted in this revisit, theoretical studies centering on the halogen-bond-forming ability of halogen’s electrophilic π-/p-holes (or π-/p-belts) in molecular entities with nucleophiles are rare and surely an important area worthy of further investigation. The development of a hole/belt may be realized as a result of “bond polarization” within the domain of the molecule, a view consonant with that of others …”
Section: Discussionsupporting
confidence: 56%
“…The development of a hole/belt may be realized as a result of "bond polarization" within the domain of the molecule, a view consonant with that of others. 335 We believe that invoking the concept of the σand π-/p-holes and orbital-based charge transfer characteristics, among others, assists in the recognition and basic understanding of the halogen bond and other noncovalent interactions. The formation of halogen bonds between sites of opposite charge capacity fits within the theoretical framework of a Coulombic attraction, but it should be appreciated that the overall stability of the complex chemical system is the result of a delicate balance between different types of attraction (i.e., electrostatics, dispersion and induction/polarization) and repulsion (e.g., exchange repulsion), in which the net interaction/binding energy is difficult to dissect.…”
Section: ■ Concluding Remarksmentioning
confidence: 99%
“…Tuning the strength of the hydrogen or halogen bond interaction for a fixed acceptor or Lewis base can be made through the interplay of a number of factors pertaining the D-H or the D-Hal donor group. With more than one type of halogen atom that can be used in D-Hal, the halogen bond also renders greater flexibility for fine-tuning compared with the hydrogen bond [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. One factor that can be used to fine tune the D-H or the D-Hal donor ability is the electronegativity of the atom covalently bonded to hydrogen or halogen.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the halogen bond donor ability of D-Hal, it has been found that both the size and the magnitude of the positive electrostatic potential (known as the σ-hole) of the halogen atom increases with the increasing electronegativity of the atom covalently bonded to the halogen atom in D-Hal. It is worth noting that the σ-hole on the halogen atom acts as the Lewis acid site that interacts with a suitable electron donor species acting as the Lewis base, and that the location of the σ-hole (opposite to the covalent D-Hal bond) results in the highly distinctive linearity of the halogen bond [ 9 , 32 , 44 ]. Further studies have demonstrated that the ability of a halogen atom to engage in halogen bonding correlates with the size of the σ-hole.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction, schematized as R–X···B (X = Cl, Br, or I; B = Lewis base; R = substituent), has been explained by the existence of a region of positive electrostatic potential, named σ-hole, on the outermost surface of the covalently-bonded halogen atom and narrowly confined on the elongation of the R–X covalent bond axis [ 20 ]. Its presence has been recently demonstrated through valence bond spin-coupled calculations [ 21 ], allowing to get a rigorous ab initio validation of the qualitative models previously proposed [ 20 ]. The key role of the σ-hole in activating XB has been particularly emphasized by molecular mechanics/molecular dynamics simulations of halogen-bonded ligand–protein systems.…”
Section: Introductionmentioning
confidence: 99%